FORECASTING RICE PRODUCTION WITH THE HOLT-WINTERS EXPONENTIAL SMOOTHING METHOD - Salamah, Nur; Intahaya, Ari Maulidah; Alfiani, Faradillah Siska; Ummah, Hidayatul; Fadhlia, Zahrotul Wardah; Isro'il, Ahmad (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
This study aims to forecast rice production in East Java using the Holt-Winters Exponential Smoothing method which can be used to view data with seasonal and trend patterns. The rice production data used in this study comes from the Central Bureau of Statistics (BPS) which includes production data for the last five years. The results of the analysis show that this method provides a sufficient level of accuracy in forecasting and is also effective in providing estimates of rice production as well as assisting in strategic decision-making on the management of the agricultural sector and food security.